The use of passiflora in the treatment of anxiety disorders in post COVID-19 times: An integrative review (Research, Society and Development, 2024)
Anxiety is an emotional state that consists of an adaptive response of the organism to threatening situations and is considered, to some extent, a physiological condition. Anxiety disorders have shown a significant increase after the COVID-19 pandemic, being associated with factors such as social isolation, fear of contagion/hospitalization, the loss of family members, as well as the interruption of psychiatric and psychological services. Different species of Passiflora sp., popularly known as passionflower or medicinal passion fruit, have calming and sedative effects on the central nervous system (CNS). The active compounds present in passionflower modulate serotonergic activity and enhance GABAergic activity, the latter being similar to the action of benzodiazepines. The objective of this study, given the increase in cases of anxiety during and after the COVID-19 pandemic, was to evaluate the use of Passiflora as a treatment for anxiety, through an integrative review of the literature. According to the reviewed studies, it was evident that herbal remedies containing Passiflora sp. are important medicinal alternatives for treating anxiety, as they not only prove effective in treating generalized anxiety disorders but are also readily available and have a lower incidence of adverse effects when compared to first-line medications such as antidepressants and benzodiazepines. Finally, the list of therapeutic and economic benefits for expanding the use of herbal remedies containing Passiflora sp. is extensive, particularly in developing countries like Brazil, which have high rates of anxiety disorders and chemical dependence on psychotropic drugs.